Methylene blue and ascorbate interfere with the accurate determination of the kinetic properties of IDO2. (26th March 2021) - Yuasa, Hajime J.; Stocker, Roland
Abstract : Indoleamine 2, 3‐dioxygenases (IDOs) catalyze the oxidative cleavage of L‐tryptophan (Trp) to N ‐formylkynurenine. Two IDOs, IDO1 and IDO2, are present in vertebrates. IDO1 is a high‐affinity Trp‐degrading enzyme involved in several physiological processes. By comparison, IDO2 generally has been reported to have low affinity (high K m ‐value) for Trp, and the enzyme's in vivo function remains unclear. Using IDOs from different species, we show that compared with ferrous‐oxy (Fe 2+ –O2 ) IDO1, Fe 2+ –O2 IDO2 is substantially more stable and engages in multiple turnovers of the reaction in the absence of a reductant. Without reductant, Fe 2+ –O2 IDO2 showed K m ‐values in the range of 80–356 μM, that is, values substantially lower than reported previously and close to the physiological concentrations of Trp. Methylene blue and ascorbate (Asc), used commonly as the reducing system for IDO activity determination, significantly affected the enzymatic activity of IDO2: In combination, the two reductants increased the apparent K m ‐ and k cat ‐values 8‐ to 117‐fold and 2‐fold, respectively. Asc alone both activated and inhibited IDO2 by acting as a source of electrons and as a weak competitive inhibitor, respectively. In addition, ferric (Fe 3+ ) IDO1 and IDO2 exhibited weak dioxygenase activity, similar to tryptophan 2, 3‐dioxygenase. Our results shed new light in the enzymatic activity of IDO2, and they support the view that this isoform of IDO also participates in the metabolism of Trp in vivo . Abstract : Methylene blue (MB) plus ascorbate (Asc) are used most commonly as the reducing system for in vitro IDO activity assays. However, Asc both activates and inhibits IDO2 by acting as an electron source and competitive inhibitor, respectively. MB also inhibits IDO2 at low substrate concentrations. These activities of MB plus Asc are the cause for the overestimation of previously reported K m‐values of IDO2 for L‐tryptophan.